Aboriginal Women Learning on Country: Lessons for Educators - Goldberg, Lynette R.; Baldock, Dianne; Cox, Terrance; Hoang, Ha; Cross, Merylin; Price, Andrea D. (Frontiers in Public Health, 2022)
Introduction: This paper details the journey of eight Aboriginal women from Circular Head, a rural and remote area of North West Tasmania, as they undertook an innovative two-year program of tertiary studies in dementia to address a documented community need. Methods: The nationally funded program included a year-long face-to-face vocational Certificate III in Individual Support (Ageing, Home, and Community) on Country, including within-community experience with adults with dementia. This face-to-face learning was combined with online study in the award-winning Bachelor of Dementia care offered by the University of Tasmania. Students received a PhD level stipend to support them in their studies and were guided by an Elder from their community. Results: All students completed their Certificate III. The number of units they completed towards the eight required for their initial Diploma of Dementia Care varied. Data from this mixed methods approach documented the impact of the innovative coupling of authentic, culturally appropriate experiential learning with broad and deep academic knowledge about dementia and evidence-based care. Conclusions: This program provided students with a work-related qualification embedded within a university education and increased the capacity and capability of this Aboriginal community to provide care for its members with dementia, a documented concern. The combination of vocational learning on Country with online university study established a pathway to improve students’ access to and success in higher education and the professional workforce. This assisted in counteracting the negative influences of racism, stigma, rurality, and socio-economic marginalization on educational opportunity for Aboriginal people. Data showed the need for flexibility with this learning journey, and the strengths and resilience of these women as they learned.